2014
DOI: 10.3897/zookeys.404.7234
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding as a screening tool for cryptic diversity: an example from Caryocolum, with description of a new species (Lepidoptera, Gelechiidae)

Abstract: We explore the potential value of DNA barcode divergence for species delimitation in the genus Caryocolum Gregor & Povolný, 1954 (Lepidoptera, Gelechiidae), based on data from 44 European species (including 4 subspecies). Low intraspecific divergence of the DNA barcodes of the mtCOI (cytochrome c oxidase 1) gene and/or distinct barcode gaps to the nearest neighbor support species status for all examined nominal taxa. However, in 8 taxa we observed deep splits with a maximum intraspecific barcode divergence bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Lepidoptera, the most intensively studied order, is represented by more than 100 000 BINs on BOLD. Work on this group has demonstrated the efficacy of DNA barcoding in identifying known species (Wilson et al 2013;Dinca et al 2015) and in revealing cryptic species complexes (Burns et al 2008;Huemer et al 2014a). It has also shown that there is very limited geographic variation in barcode sequences in populations of most species, so increased geographic scale does not reduce the success of species identification (Lukhtanov et al 2009;Huemer et al 2014b, Candek andKuntner 2015).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Lepidoptera, the most intensively studied order, is represented by more than 100 000 BINs on BOLD. Work on this group has demonstrated the efficacy of DNA barcoding in identifying known species (Wilson et al 2013;Dinca et al 2015) and in revealing cryptic species complexes (Burns et al 2008;Huemer et al 2014a). It has also shown that there is very limited geographic variation in barcode sequences in populations of most species, so increased geographic scale does not reduce the success of species identification (Lukhtanov et al 2009;Huemer et al 2014b, Candek andKuntner 2015).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Like other genera, only a single species of Megacraspedus , M.dolosellus , was considered in the aforementioned study, reflecting the general lack of molecular data and analysis at the generic level. The implementation of DNA barcoding has helped to reduce such shortcomings in the Gelechiidae for a few genera so far (Huemer and Hebert 2011, Huemer et al 2014) but restriction to the mitochondrial COI gene limits the value for phylogenetic analysis. Molecular studies at a generic level, based on a larger number of nuclear genes, are completely lacking, not least because of the limitation and quality of available voucher material and the general lack of resources.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Gelechiidae genera using DNA barcodes are exceptional and give a somewhat different picture. An analysis of 44 species of Caryocolum (Huemer et al 2014) resulted in a maximum intraspecific divergence from 0% in several species to 6.3%, and in six species the mean divergence was greater than 3%. However, most of these cases represent allopatric cryptic diversity (Huemer pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid unnecessary synonyms it may be more appropriate to refrain from new descriptions of Aenictus species until male-worker combinations are better understood, for example by applying barcoding approaches (see e.g. Huemer et al 2014). Not describing new species causes, however, a different problem.…”
Section: Discussionmentioning
confidence: 99%